Optimized CANDU-6 cell and reactivity device supercell models for advanced fuels reactor database generation. (November 2015) - St-Aubin, Emmanuel; Marleau, Guy
Highlights: Propose an optimize 2-D model for CANDU lattice cell. Propose a new 3-D simulation model for CANDU reactivity devices. Implement other acceleration techniques for reactivity device simulations. Reactivity device incremental cross sections for advanced CANDU fuels with thorium. Abstract: Several 2D cell and 3D supercell models for reactivity device simulation have been proposed along the years for CANDU-6 reactors to generate 2-group cross section databases for finite core calculations in diffusion. Although these models are appropriate for natural uranium fuel, they are either too approximate or too expensive in terms of computer time to be used for optimization studies of advanced fuel cycles. Here we present a method to optimize the 2D spatial mesh to be used for a collision probability solution of the transport equation for CANDU cells. We also propose a technique to improve the modeling and accelerate the evaluation, in deterministic transport theory, of the incremental cross sections and diffusion coefficients associated with reactivity devices required for reactor calculations.